Exploring Mahmud Yunus's Indonesian-Arabic Dictionary: Structure and Significance - Sholekhah, Hida Yatus; Hikmah, Khizanatul (Universitas Muhammadiyah Sidoarjo, 2024)
Background: This study examines Mahmud Yunus' Arabic-Indonesian dictionary using a library research method. Gap: Limited research exists on the dictionary's structural features and supplementary content. Aim: The research analyzes the dictionary's components and applies Philip Mayring's content analysis. Results: The 14th edition of the dictionary includes linguistic tools like tashrif and wazan but lacks elements such as historical chronology, maps, and compiler details. It does feature visual aids related to everyday objects. Novelty: The study reveals missing supplementary content, suggesting areas for improvement. Implications: Updates could enhance its educational value. Highlights : Library Research Method: Emphasizes the use of primary and secondary data sources for comprehensive analysis. Structural Components: Identifies key elements in the dictionary, such as tashrif and wazan, and highlights missing features like historical chronology. Educational Value: Suggests the need for updates to enhance the dictionary's utility as a linguistic resource. Keywords: Mahmud Yunus, Arabic-Indonesian dictionary, content analysis, linguistic tools, supplementary features